2000
DOI: 10.1073/pnas.97.4.1885
|View full text |Cite
|
Sign up to set email alerts
|

Induction of topoisomerase I cleavage complexes by 1-β- d -arabinofuranosylcytosine (ara-C) in vitro and in ara-C-treated cells

Abstract: 1-␤-D-Arabinofuranosylcytosine (Ara-C) is a nucleoside analog commonly used in the treatment of leukemias. Ara-C inhibits DNA polymerases and can be incorporated into DNA. Its mechanism of cytotoxicity is not fully understood. Using oligonucleotides and purified human topoisomerase I (top1), we found a 4-to 6-fold enhancement of top1 cleavage complexes when ara-C was incorporated at the ؉1 position (immediately 3) relative to a unique top1 cleavage site. This enhancement was primarily due to a reversible inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 34 publications
2
102
1
Order By: Relevance
“…Although the exact nature of the damage caused by nucleoside analogs in stalling replication forks is poorly understood, it follows that cellular responses to these agents are likely to overlap those elicited by drugs such as hydroxyurea (HU) that also cause replication forks to stall by limiting dNTP production. Also, crystallographic studies have demonstrated that incorporation of ara-C into DNA causes localized alterations in the DNA duplex (Schweitzer et al, 1994) and stabilizes covalent topoisomerase I-DNA complexes, thus converting the enzyme into a cellular poison (Pourquier et al, 2000;Chrencik et al, 2003). This suggests that cellular responses to nucleoside analogs are also likely to overlap those elicited by the camptothecin family of topoisomerase I active agents.…”
Section: Sensors Of Dna Damage In Replicating Cellsmentioning
confidence: 99%
“…Although the exact nature of the damage caused by nucleoside analogs in stalling replication forks is poorly understood, it follows that cellular responses to these agents are likely to overlap those elicited by drugs such as hydroxyurea (HU) that also cause replication forks to stall by limiting dNTP production. Also, crystallographic studies have demonstrated that incorporation of ara-C into DNA causes localized alterations in the DNA duplex (Schweitzer et al, 1994) and stabilizes covalent topoisomerase I-DNA complexes, thus converting the enzyme into a cellular poison (Pourquier et al, 2000;Chrencik et al, 2003). This suggests that cellular responses to nucleoside analogs are also likely to overlap those elicited by the camptothecin family of topoisomerase I active agents.…”
Section: Sensors Of Dna Damage In Replicating Cellsmentioning
confidence: 99%
“…So far, it could be shown that htopoI cleavage complex formation arises in response to various DNA damaging treatments in cultured cells (Subramanian et al, 1998;Pommier et al, 2000;Pourquier et al, 2000Pourquier et al, , 2001Pourquier et al, , 2002Daroui et al, 2004;Soe et al, 2004;Sordet et al, 2004a, b). Previously, it was discussed that htopoI molecules could be trapped due to a direct recognition of the DNA damage, followed by cleavage of the DNA strand.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fact that numerous chemotherapeutic drugs seem to kill tumor cells, for example by inducing htopoI cleavage complexes (Pourquier et al, , 2002Sordet et al, 2004b), makes the htopoI damage response a highly relevant and important pathway to analyse in further detail, since the so obtained knowledge may help to improve or understand the action of chemotherapeutics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Besides, further investigation indicates inhibition of topoisomerase I as an additional mechanism for ara-C cytotoxicity. 3 In clinical studies, cellular accumulation and retention of ara-CTP have been correlated with manifestations of ara-Cmediated cytoxicity and clinical outcome. [4][5][6] Resistance against ara-C is the major cause of treatment failure.…”
Section: Introductionmentioning
confidence: 99%